Double Length Regressions for Testing the Box-Cox Difference Transformation - Park, Timothy (The Review of Economics and Statistics, 1991)
The Box-Cox difference transformation is used to determine the appropriate specification for estimation of hedge ratios and a new double length regression form of the Lagrange multiplier test is presented for the difference transformation. The Box-Cox difference transformation allows the testing of the first difference model and the returns model as special cases of the Box-Cox difference transformation. Copyright 1991 by MIT Press.